Serum Soluble TACI, a BLyS Receptor, Is a Powerful Prognostic Marker of Outcome in Chronic Lymphocytic Leukemia. (5th August 2014) - Kyrtsonis, Marie-Christine; Sarris, Katerina; Koulieris, Efstathios; Maltezas, Dimitrios; Nikolaou, Eftychia; Angelopoulou, Maria K.; Bartzis, Vassiliki; Tzenou, Tatiana; Dimou, Maria; Siakandaris, Mariana P.; Viniou, Nora A.; Sachanas, Sotirios; et al.
Abstract : BLyS is involved in CLL biology and its low soluble serum levels related to a shorter time to first treatment (TFT). TACI is a BLyS receptor and can be shed from cells' surface and circulate in soluble form (sTACI). We investigated the impact of serum BLyS and sTACI levels at diagnosis in CLL patients and their relationship with disease parameters and patients' outcome. Serum BLyS was determined in 73 patients, while sTACI in 60. Frozen sera drawn at diagnosis were tested by ELISA. sTACI concentrations correlated with BLyS (P = - 0.000021 ), b2-microglobulin (P = 0.005 ), anemia (P = - 0.03 ), thrombocytopenia (P = 0.04 ), Binet stage (P = 0.02 ), and free light chains ratio (P = 0.0003 ). Soluble BLyS levels below median and sTACI values above median were related to shorter TFT (P = 0.0003 and 0.007). During a ten-year followup, sTACI levels, but not BLyS, correlated with survival (P = 0.048 ). In conclusion, we confirmed the prognostic significance of soluble BLyS levels with regard to TFT in CLL patients, and, more importantly, we showed for the first time that sTACI is a powerful prognostic marker, related to parameters of disease activity and staging and, more importantly, to TFT and OS.